Cognition and inflammation: “the role of cytokines in cognitive performance” - Jorge Mauricio Cuartas Arias (Universidad de San Buenaventura, 2014)
The interactions between the immune system and nervous system have been the focus of research in recent years. Perhaps due to the discovery and acknowledgement of the multiple functions that cytokines carry out in the central nervous system (CNS), going from mediators of neuropathologic processes to the degeneration and repair within the CNS.